Vulnerability of Rural Properties in the Pantanal Amid Recent Exceptional Environmental Changes - PABLO PINHEIRO DUTRA (2023)
This study analyzed recent exceptional environmental changes (REECs) in the Pantanal, focusing on rural properties of various sizes affected. The results highlight that REECs do not occur uniformly in space and disproportionately affect properties of different sizes. Small properties were particularly impacted by exceptional fires, which has significant implications as these areas house communities with limited resources and rely on subsistence agriculture. Strategies for fire prevention and control, income source diversification, and strengthening the adaptive capacity of these communities are recommended to reduce vulnerability to these changes. Our study underscores the importance of targeted interventions tailored to local needs and collaboration to promote the resilience of communities affected by REECs in the Pantanal.